Formability optimisation of fabric preforms by controlling material draw-in through in-plane constraints - Chen, S.; Harper, L.T.; Endruweit, A.; Warrior, N.A. (Elsevier, 2015)
A genetic algorithm is coupled with a finite element model to optimise the arrangement of constraints for a composite press-forming study. A series of springs are used to locally apply in-plane tension through clamps to the fibre preform to control material draw-in. The optimisation procedure seeks to minimise local in-plane shear angles by determining the optimum location and size of constraining clamps, and the stiffness of connected springs. Results are presented for a double-dome geometry, which are validated against data from the literature. Controlling material draw-in using in-plane constraints around the blank perimeter is an effective way of homogenising the global shear angle distribution and minimising the maximum value. The peak shear angle in the double-dome example was successfully reduced from 48.2 degrees to 37.2 degrees following a two-stage optimisation process.